2013
DOI: 10.1590/1678-7757201300004
|View full text |Cite
|
Sign up to set email alerts
|

CCL3 and CXCL12 production in vitro by dental pulp fibroblasts from permanent and deciduous teeth stimulated by Porphyromonas gingivalis LPS

Abstract: Objective:The aim of this study was to compare the production of the chemokines CCL3 and CXCL12 by cultured dental pulp fibroblasts from permanent (PDPF) and deciduous (DDPF) teeth under stimulation by Porphyromonas gingivalis LPS (PgLPS).Material and Methods:Primary culture of fibroblasts from permanent (n=3) and deciduous (n=2) teeth were established using an explant technique. After the fourth passage, fibroblasts were stimulated by increasing concentrations of PgLPS (0 - 10 µg/mL) at 1, 6 and 24 h. The cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 39 publications
3
33
1
8
Order By: Relevance
“…Barrett's esophagus (BAR-T cell line) were stimulated with the TLR4 agonist lipopolysaccharide (LPS).It was shown that stimulation of TLR4 with LPS resulted in NF-κB activation and an increase of IL-8 secretion (Verbeek et al 2014). In fact, the structure of the LPS of Porphyromonasgingivalis (PgLPS) has a further particular antigenic moiety and is recognized by TLR2, which is responsible for the recognition of cell wall components of gram positive bacteria (Sipert et al 2013). Genetic studies have been performed on TLR polymorphisms in esophageal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Barrett's esophagus (BAR-T cell line) were stimulated with the TLR4 agonist lipopolysaccharide (LPS).It was shown that stimulation of TLR4 with LPS resulted in NF-κB activation and an increase of IL-8 secretion (Verbeek et al 2014). In fact, the structure of the LPS of Porphyromonasgingivalis (PgLPS) has a further particular antigenic moiety and is recognized by TLR2, which is responsible for the recognition of cell wall components of gram positive bacteria (Sipert et al 2013). Genetic studies have been performed on TLR polymorphisms in esophageal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Teeth and gingival tissues were donated under patient informed consent (third molars from three adults aged 18–26, canines from three children aged 7–9). Human fibroblasts from gingiva (GF) (n=3), periodontal ligament (PLF) (n=3), dental pulp from permanent (PDPF) (n=3) and deciduous (DDPF) (n=3) teeth were cultured using an explant technique as described previously (6,7,9,23). Tissues were fragmented and individually incubated for cell growth in Dulbecco’s modified Eagle’s medium (DMEM) (Invitrogen, Life Technologies Corporation, Carlsbad, USA) supplemented with 10% fetal bovine serum (FBS) (Gibco, Invitrogen) and antibiotics (100 μg/mL penicillin, 100 μg/mL streptomycin, 0.5 mg/mL amphotericin B – Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Cultured cells were characterized as fibroblasts by their morphology and positivity for Fibroblast Specific Protein-1 (FSP-1) (9,24). Immunostaining was performed using mouse anti-human FSP-1 (1B10) (Abcam, Cambridge, UK) followed by fluorescein conjugated anti-mouse IgG (Abcam).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been clearly demonstrated that the biological behavior of fibroblasts is related to the type of connective tissue from which they originate (2)(3)(4). Such properties include membrane receptor expression (3) and cytokine release kinetics (2,3,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%